2015
DOI: 10.1007/s13277-015-3296-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor suppressor gene SOX11 in prostate cancer

Abstract: SOX genes play an important role in a number of developmental processes. The transcription factor SOX11 is one of the members of the SOX family emerging as important transcriptional regulators. The aim of this study was to investigate the role of SOX11 in prostate cancer (PCa) and its expression pattern and clinical significance. The gene expression of SOX11 in human PCa tissues compared with benign prostate hyperplasia (BPH) tissues was detected using real-time quantitative reverse transcriptase-polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Using IHC, reverse transcription–polymerase chain reaction (RT–PCR) or Western blot, SOX11 has been found to be down‐regulated in several malignant epithelial tumours, such as prostate, gastric and nasopharyngeal carcinomas via hypermethylation, and in these epithelial tumours SOX11 functions as a tumour suppressor gene that is associated with tumour growth and invasion . In this study, SOX11 expression was completely absent in all the aforementioned carcinomas, as well as most other adenocarcinomas and carcinomas that originated from the squamous, urinary and thymic epithelia using IHC (Table ).…”
Section: Discussionmentioning
confidence: 72%
“…Using IHC, reverse transcription–polymerase chain reaction (RT–PCR) or Western blot, SOX11 has been found to be down‐regulated in several malignant epithelial tumours, such as prostate, gastric and nasopharyngeal carcinomas via hypermethylation, and in these epithelial tumours SOX11 functions as a tumour suppressor gene that is associated with tumour growth and invasion . In this study, SOX11 expression was completely absent in all the aforementioned carcinomas, as well as most other adenocarcinomas and carcinomas that originated from the squamous, urinary and thymic epithelia using IHC (Table ).…”
Section: Discussionmentioning
confidence: 72%
“…The only available experimental study suggested the potential tumour suppressor function of SOX11 in prostate carcinoma cell lines (Yao et al . ). The authors also found significant downregulation of SOX11 and low protein expression in tissue specimens (Yao et al .…”
Section: Discussionmentioning
confidence: 97%
“…The authors also found significant downregulation of SOX11 and low protein expression in tissue specimens (Yao et al . ). We hypothesized that epigenetic mechanism may be responsible for SOX11 silencing in human prostate cancer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the multiple functions of SOX genes in the development of these various systems alerted researchers to their potential roles in the development of diseases, especially cancers 12 . Most recent studies of SOX genes focused on their involvement in gastric cancer, lung cancer, hepatocellular carcinoma, and prostate cancer 2-4,28,29 . Studies indicated that most SOX genes played their roles in these cancers through the Wnt/β-catenin signaling pathway, as the so-called ‘canonical’ Wnt pathway mediated by β-catenin 12,13 .…”
Section: Classification and Functions Of Sox Genesmentioning
confidence: 99%